The ambition and political career at the Peruvian subnational level - Incio, José (Revista de Ciencia Política y Gobierno, 2016)
Politicians, their behavior and dynamics are especially relevant in context where political parties are weak and the political system has little institutionalization. In this article we try to know the different types of political career of local politicians in Peru. To this end, we have systematized and organized information- provided by the Infogob portal of the National Elections Board- (JNE)of more than 22,000 local politicians, who began their political career as mayors or district councilors at three different times: 1980, 1993 and 2002. These three milestones represent important breakthroughs in Peruvian political history, so we hypothesize that they generate different incentives, which helps us explain the ambition of the local politician and the different paths that his career takes. We show that the institutional changes resulting from the reforms of the decentralization process generate greater incentives for the local politician to have a progressive political career.